Sensing Coverage Enhancement of Cellular Networks Via Mutual Interference Suppression - Wang, Bowen; Li, Nanxi; Zhu, Jianchi; She, Xiaoming; Chen, Peng (2024 27th International Symposium on Wireless Personal Multimedia Communications (WPMC), 2024)
This paper explores sensing coverage in Integrated sensing and communication (ISAC) networks. We formulate the sensing optimization problem as a linearly constrained binary quadratic programming instance, accounting for mutual interference among base stations. Semi-definite relaxation based branch and bound method and successive convex approximation method are developed respectively for homogeneous and heterogeneous networks. The sensing coverage of any given network topology can ultimately be obtained. Numerical results demonstrate the tremendous gains of collaboration, and the feasibility of nearoptimal performance attainment with limited number of collaborating base station inputs.